FACTORS AFFECTING THE EXTERNAL POTENTIAL OF ISLAMIC EDUCATION MANAGEMENT: GLOBALIZATION, SOCIAL CHANGE, AND THE ECONOMY - Gustiar, Eri Deka; Ali, Hapzi; Rosadi, Kemas Imron (Teunuleh Publisher, 2022)
The development of educational institutions in Indonesia has been influenced by various things that are quite important in order to realize the vision, mission, and goals of educational institutions. One of them is the potential for external factors, which also affect important capabilities and strategies in decision making. The external problems of education in Indonesia today are very complex. This is due to the complex reality of the external dimensions of education itself which include social, political, economic, cultural, and even global dimensions. From these dimensional problems, three focuses of problems emerge, namely the problems of globalization, social change, and the economy. In organizing an educational institution that has the aim of compiling a pattern of activities in order to achieve common goals is strongly influenced by external and internal factors. For this reason, the purpose of this study is how to analyze the potential external factors of Islamic Education Management that can affect the process and quality of educational institutions. From the results of the literature review, several potential external factors consist of elements outside the organization / institution, most of which cannot be controlled and influential in decision making, so that the third focus of problems on the educational dimension greatly affects the External Potential of Islamic Education Management.